PENGARUH STRATEGI CRITICAL INCIDENT (PENGALAMAN PENTING) TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN FIQH KELAS VII DI MTS N KOTA BOGOR - Anjarsari, Rini; Triwoelandari, Retno; Arif, Suyud (Aksara Public, 2019)
Education is a very important requirement for humans. Based on the results of research conducted, states that student motivation is still relatively low, so we need an active learning strategy that is able to increase student motivation. Active learning strategies that can be used are Critical Incident strategies. This study aims 1) To determine the motivation for fiqh learning in class VII through critical incident strategies in MTs N Bogor City, 2) To determine the effect of Critical Incident strategy on fiqh learning motivation in class VII MTs N in Bogor City. This research method uses a quantitative approach with quasy experiment method or also called pseudo experiment. This research was conducted in seventh grade students of MTs N Bogor City. The results showed through the t-test the value of tcount was 6.299 with a significance of 0,000. Significance value that shows 0,000 <0.005 so that (Ho) is rejected and (Ha) is accepted. This is also supported by the mean value of the experimental class of 61.81 greater than the control class of 55.97. Thus, it can be concluded that the critical incident strategy has an effect on student motivation in class VII MTs N Bogor City.